Optimization of Multi-Effect Evaporation desalination plants - Druetta, Paula (2013)
This paper focuses on the mathematical modeling and optimization of Multi-Effect Evaporation plants (MEE). A simplified and detailed enough model to accurately predict the MEE system performance is presented. The model is highly nonlinear and it is based on mass and energy balances which are derived from a superstructure. The superstructure involves several process configurations which have to be simultaneously optimized to determine the best stream flow-patterns (synthesis), the size of each evaporation effect (sizing) and the operating conditions of the whole process. Beside the conventional configuration, the model also includes different alternative flow- patterns for the distillate and the vapor streams. An equation-oriented environment was selected to develop and implement the model, allowing different application instances, such as simulation, sensitivity analysis and optimization, to be easily performed. Simulation results have shown a good agreement with realistic design data and other authors´ results. A ranking of themodel parameters is presented according to their impact on the heat transfer area. Moreover, optimization results showed that themodification of the flowpatterns improve the process performance, reducing the process specific total heat transfer area in about 5% compared to the optimal value of the conventional case.